Analysis of Vitamin C Level Contained in Mango Gadung (Mangifera indica L) With Varied Retention Time - Anjar Purba Asmara (Elkawnie: Journal of Islamic Science and Technology, 2016)
This research is aimed to determine the level of vitamin C in the mango Gadung which stored as long as 0 days; 1 day; 2 days; and 3 days. It is used iodimetric titration. Standard iodine solution used as titrant while starch as the indicator. Determination of raw normality iodine standardization carried out by titration of iodine with sodium thiosulphate solution primer. Normality primary sodium thiosulphate solution (0.0125 N) are determined through standardized sodium thiosulphate with potassium dichromate. Levels of vitamin C in the fruit is determined by linear regression analysis were made based on the graph of the vitamin C levels versus volume of iodine standard solution which used in the titration. The curve gives the equation as following: y = 413.8 x – 1.238. Levels of vitamin C of mango Gadung which has varied retention time as follows: 0.26% (0 days); 0.22% (1 day); 0.20% (2 days); and 0.16% (3 days).